Investigasi dan Evaluasi Hasil Temperatur Pemotongan dengan Berbagai Kondisi dan Parameter Pendinginan pada Proses Pemesinan Milling - Habiby , Nuril Anwar; Abdillah, Moh. Bima Fahrosyid Rizki; Habsah, Ilvia (Jurnal Studi Multidisiplin Qomaruna, 2025)
In the manufacturing industry, especially those engaged in the machining process, the results of product quality and tool life are always the main focus of the industry. These factors can be influenced by the friction that occurs between the cutting tool or chisel and the workpiece during the machining process which will cause high cutting temperatures so that the cutting temperature problem must be resolved immediately. This study aims to analyze the effect of machining parameters and conditions on the cutting temperature in the milling machining process. Variations in machining conditions and parameters used include dry, flood, and air-cooling techniques; Spindle speed parameters 500, 800, and 1100 rpm; Feed rate parameters 60, 100, and 140 mm/min. The method used is an experimental method. The cutting temperature was measured using an infrared thermometer. The results of the analysis in this study indicate that the combination of variables in the milling machining process that obtains the most optimal response value to reduce the cutting temperature is the use of the flood coolant cooling technique, then a spindle speed of 800 rpm, and a feed rate of 100 mm/min.